Monday

March 2, 2015

March 2, 2015

Posted by **Maths** on Tuesday, August 20, 2013 at 1:48pm.

f(x)=x2 + px + q

Prove that:

f(x+1) + f(x-1)= 2+2 f(x)

- Maths -
**Steve**, Tuesday, August 20, 2013 at 2:40pmjust plug in the values:

f(x+1) = (x+1)^2 + p(x+1) + q

f(x-1) = (x-1)^2 + p(x-1) + q

add them to get

2x^2 + 2 + 2px + 2q

2(x^2+px+q) + 2

2f(x) + 2

- Maths -
**plsHelp**, Tuesday, August 20, 2013 at 4:37pmSteve thanks very much, may i have your email id so i can ask a question with integrals/limits which i cant write here

**Answer this Question**

**Related Questions**

Maths Derivatives & Calulus - 1) Find d^2y / dx^2 given that y^3 - x^2 = 4 2)If ...

Geometry - Can you just help me with this thanks Directions: Tell which property...

maths - Given that a,b,c >0 Prove : (a/b + b/c +c/a)(b/a +c/b +a/c)>0

maths - given function G(x)=1/3(x-2)^2-3 2<x<5 sketch a graph of function ...

maths - prove that the following function is differentiable at x=0 using first ...

Math - Mathematical Induction - 3. Prove by induction that∑_(r=1)^n▒...

math - Given: ; CE=CA ,EB AND AD are medians Prove: EB=AD 2.)Write a paragraph ...

Geometry - Given: UR=VW Prove: UV=RW(Midpoint) Given: angleABE=angleDBC(...

algebra - Give am example of a function f.N N with the property that there ...

maths - If the sum of the squares of the roots of the quadratic equation ax^2 + ...